The Effect of Electrode Designs Based on the Anatomical Heart Location for the Non-Contact Heart Activity Measurement. - Gi, Sun; Lee, Young-Jae; Koo, Hye; Lee, Seung; Lee, Kang-Hwi; Kim, Kyeng-Nam; Kang, Seung-Jin; Lee, Joo; Lee, Jeong-Whan (Journal of Medical Systems, 2015)
This research is an extension of a previous research [] on the different effects of sensor location that is relatively suitable for heart rate sensing. This research aimed to elucidate the causes of wide variations in heart rate measurements from the same sensor position among subjects, as observed in previous research [], and to enhance designs of the inductive textile electrode to overcome these variations. To achieve this, this study comprised two parts: In part 1, X-ray examinations were performed to determine the cause of the wide variations noted in the findings from previous research [], and we found that at the same sensor position, the heart activity signal differed with slight differences in the positions of the heart of each subject owing to individual differences in the anatomical heart location. In part 2, three types of dual-loop-type textile electrodes were devised to overcome variations in heart location that were confirmed in part 1 of the study. The variations with three types of sensor designs were compared with that with a single-round type of electrode design, by using computer simulation and by performing a t-test on the data obtained from the experiments. We found that the oval-oval shaped, dual-loop-type textile electrode was more suitable than the single round type for determining morphological characteristics as well as for measuring appropriate heart activity signals. Based on these results, the oval-oval, dual-loop-type was a better inductive textile electrode that more effectively overcomes individual differences in heart location during heart activity sensing based on the magnetic-induced conductivity principle.